2015
DOI: 10.2147/clep.s78145
|View full text |Cite
|
Sign up to set email alerts
|

Statin prescription patterns, adherence, and attainment of cholesterol treatment goals in routine clinical care: a Danish population-based study

Abstract: PurposeTo examine the annual rate and cumulative prevalence of statin use in Denmark 2004–10, including adherence of use and attainment of cholesterol targets.MethodsWe included all individuals aged 18–86 years with a first statin prescription in Northern Denmark in 2004–10. We calculated the annual rate and cumulative prevalence of statin use. We examined cholesterol values before and after start of statins and the proportion reaching targets according to European guidelines and cardiovascular risk group.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 18 publications
5
41
1
2
Order By: Relevance
“…The rate of discontinuation was 12%, which is within the range reported earlier 2, 3, 6, 10, 11, 41, 42. Some previous studies have found that patients with cardiovascular comorbidities are less likely to discontinue statin use than those free of such comorbidities 3, 20, 43.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The rate of discontinuation was 12%, which is within the range reported earlier 2, 3, 6, 10, 11, 41, 42. Some previous studies have found that patients with cardiovascular comorbidities are less likely to discontinue statin use than those free of such comorbidities 3, 20, 43.…”
Section: Discussionsupporting
confidence: 80%
“…Some previous studies have found that patients with cardiovascular comorbidities are less likely to discontinue statin use than those free of such comorbidities 3, 20, 43. However, a recent Danish, population-based study of 161, 646 new statin users reported discontinuers to have a slightly higher prevalence of almost all the examined diagnoses of comorbidity, including cardiovascular disease 11 . A major limitation of that study was its reliance on registered data only.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…That said, it is also possible that cancer patients would be distracted from taking medications directed at cardiovascular disease, in which case these results might underestimate adherence in an otherwise healthy population. We found the same medication possession ratio as reported in a population‐based study in the Northern Denmark, suggesting that our results may be widely generalizable.…”
Section: Discussionsupporting
confidence: 87%
“…Statins are one of the most commonly prescribed medications [1, 2]. Over 25% of Americans over the age of 45 years are prescribed a statin according to a CDC study from 2010 [3].…”
Section: Introductionmentioning
confidence: 99%